Johnny Careless : a novel [large type] - Wade, Kevin (Thorndike Press large print high octane., 2025)
"Police Chief Jeep Mullane has been bounced back home to Long Island's North Shore by a heartbreaking case that both earned him his NYPD detective's shield and burned him out of the Job. Now heading up a small local police department, he finds himself navigating the same geography he did growing up there as the son of an NYPD cop. Jeep is a "have-not" among the glittering "haves," a sharp-witted, down-to-earth man in a territory defined and ruled by multigenerational wealth and power and the daunting tribal codes and customs that come with it. When the corpse of Jeep's childhood friend Johnny Chambliss--born into privilege and known as "Johnny Careless" for his reckless, golden-boy antics--surfaces in the Bayville waters, past collides with present, and Jeep is pulled into a treacherous web. He is challenged by Johnny's wealthy and secretive family and his beautiful, enigmatic ex-wife as he untangles a knotted mystery fraught with theft, corrupt local moguls, and decades-old secrets, all while grappling with his own deep-seated grief for his lost pal"--